DEVELOPMENT OF FAST - STRENGTH QUALITIES IN A GYMNAST (Web of Teachers: Inderscience Research, 2023)
The article is devoted to the issues of voluntary training of athletes. Concepts of will and volitional actions, volitional qualities, contribution to achieving high results in sports activities.